ANALISIS PEMBEBANAN TRANSFORMATOR GARDU SELATAN KAMPUS UNIVERSITAS TADULAKO - Kongah, Dendi; Sarjan, Muh.; Mukhlis, Baso (-)
Abstract Electrical system Tadulako University has problems voltage drop and load unbalance caused by the distance network connecting the distribution substation and the supplied building is so far. Moreover, the load distribution is irregular resulting in drop voltage and load imbalance. This study is specifically addressed to discuss the problems occurred in Gardu Selatan Universitas Tadulako, where the substation is supplying the load to the Fakultas Pertanian, Fakultas Kehutanan, Fakultas Teknik, Fakultas MIPA, FKIK, and several other new buildings. The method used is to measure the current and voltage on the transformer and also on the panels in the building who experience a voltage drop by using Amperes pliers. The results of the measurements and analysis are that the 185 Volt low voltage drop has passed the standard provisions PUIL where the voltage drop across the low voltage network is 4%. This is because the area supplied by the substation south very wide and long enough network that reaches 804 meters so far has exceeded the provision SPLN maximum of 350 meters. It is therefore necessary to transfer electricity network path between distribution substations closer to the buildings in the supply. To avoid load unbalance it is necessary precision in any additional load on each phase and phase transfer loads to smaller current values ​​measured during peak load. Keywords: Drop Voltage, Load unbalance, distribution substation.